Math, asked by saurav163, 1 year ago

how to expand: (3a-5b-c)² tell me

Answers

Answered by QUEEN007
3
Hey Friend ☺

( 3a - 5b - c ) ^2

Using identity ( a + b + c )^2 = a^2 + b^2 + c^2 + 2 ( ab + bc + ac )

Here a = 3a , b = - 5b , c = - c

so

( 3a - 5b - c )^2

= ( 3a )^2 + ( - 5b )^2 + ( - c )^2 + 2 [ ( 3a )( - 5b ) + ( - 5b )( - c ) + ( 3a )( - c )

= 9a^2 + 25b^2 + c^2 + 2 ( - 25ab + 5bc - 3ac )

= 9a^2 + 25b^2 + c^2 - 50ab + 10bc - 6ac

Hope it helps you ..!!

Answered by Srishti14311
1
(3a-(5b+c))^2
And then first solve this by (a-b)^2 and then (a+b)^2 =(5b+c)^2
Similar questions